Systemic metastasis in malignant solitary fibrous tumor of the liver: two case reports and literature review - Wei, Pengcheng; Lo, Chen; Gao, Jie; Zhu, Jiye; Sun, Xin; Li, Zhao (Frontiers in Oncology, 2024)
Solitary fibrous tumor of the liver (SFTL) is an exceptionally rare mesenchymal tumor, with only 117 cases reported in the literature. While most SFTs are benign, some exhibit malignant behavior, including local recurrence and metastasis. This report presents two cases of SFTL with systemic metastases, both involving prior intracranial tumors. The first case, a 52-year-old woman, discovered a liver mass incidentally during a routine physical exam. Subsequent investigations revealed potential bone metastasis, and biopsy confirmed SFT. She received two TACE procedures, anlotinib targeted therapy, and radiotherapy for the iliac bone lesion, resulting in stable disease with reduction in lesion size. The second case, a 46-year-old man, presented with multiple liver, pelvic, and lung lesions following pelvic tumor resection, with pathology confirming SFT. He was treated with long-term anlotinib therapy, CyberKnife for hepatic, lung, and pelvic lesions, and radiofrequency ablation for hepatic lesions. Postoperative recovery was uneventful, with no tumor progression on follow-up. SFTL presents with atypical clinical and imaging features, and diagnosis requires pathological and genetic confirmation. Radical resection is preferred for solitary tumors, while comprehensive treatment, including surgery and long-term follow-up, is essential for cases with recurrence or metastasis.